Boron nitride nanosheet-induced low dielectric loss and conductivity in PVDF-based high-k ternary composites bearing ionic liquid. (March 2021) - Feng, Yefeng; Chen, Peiyao; Zhu, Qiuyin; Qin, Ben; Li, Yandong; Deng, Qihuang; Li, Xianping; Li, Xiaoxiao; Peng, Cheng
Graphical abstract: Abstract: Composite dielectrics with high permittivity, low dielectric loss and low conductivity are desired. Low loss and low conductivity are difficult to achieve due to the poor interfacial compatibility and high leakage conductance. In this work, polymer/ionic liquid (IL)/hexagonal boron nitride (h-BN) nanocomposites were fabricated. A synergy between IL and BN was found. The blocked conductive path and reduced dipole coupling contributed to reduced loss and conductivity. Polyvinylidene fluoride (PVDF) was used as the polymeric matrix. The 1-butyl-3-methylimidazolium hexafluorophosphate IL with a high interface compatibility onto PVDF was employed as an organic filler. The ultrahigh polarity of IL contributed to the improved permittivity. BN, with an ultrahigh insulation property, was utilized as an inorganic filler. The BN could block the conductive path and reduce the coupling between the ionic dipoles in the IL. Compared with PVDF/IL composites, the ternary composites showed improved overall electrical properties. The ternary composite with 1.5 wt % IL and 5.0 wt % BN had a high permittivity of ∼46, low loss of ∼0.23 and low conductivity of ∼2.49 × 10 −7 S m -1 at 100 Hz. This work might offer the design ideas for the promising composite dielectrics.